AB0080 Association between life events and rheumatoid arthritis, results from the eira case control study. (23rd January 2014) - Wesley, A.; Bengtsson, C.; Skillgate, E.; Saevarsdottir, S.; Theorell, T.; Holmqvist, M.; Klareskog, L.; Alfredsson, L.; Wedrén, S.
Abstract : Background: Stressful life events can be divided into critical events, i.e. events with a defined onset and duration (earthquake, fire ), and chronic events with undetermined onset and duration, i.e. chronic life difficulties (impaired economic situation, unemployment) (Theorell 2012). Exposure to psychological stress activates the immune system via both the hypothalamus-pituitary-adrenal axis (HPA axis) and the autonomic nervous system (LeResche and Dworkin 2002). Exposure to long-term stress disturbs the HPA activity and results in an altered response of the immune system to acute stress and increases the vulnerability to illness (Huyser and Parker 1998; McEwen 1998; Crofford 2002). Objectives: To investigate the effects of stressful life events on the risk of developing rheumatoid arthritis (RA), in women and men and with or without antibodies towards citrullinated peptides Methods: A population based case-control study of individuals aged 18 to 70 years, living in geographically defined parts of Sweden between May 1996 and November 2009. We included incident cases (n=2774) diagnosed by rheumatologists according to the American College of Rheumatology 1987 criteria for RA. Controls (n=3911) were matched by age, sex, and geographical area of residence. All answered a self-administered questionnaire. We calculated odds ratios (OR) and 95% confidence intervals (CI) from unconditional logistic regression models adjusted for matching and confounding factors. Results: Having experienced a life event was weakly but significantly associated with ACPA positive and ACPA negative RA, OR 1.1, 95%CI 1.0-1.2, and 1.2 95%CI 1.0-1.4, respectively. There was a clear but non-significant trend of increasing strength of association with ACPA negative RA with increasing numbers of events. Results were the most consistent in women. We found several separate life events to be associated with RA in women. The perceived impact of the event and how long before disease onset it occurred slightly affected some associations. Conclusions: We found that stressful life events were associated with RA incidence. The associations were weak but clear, presumably indicating complexity in the net impact of stress on individuals. References: Theorell, T. (2012). "Evaluating life events and chronic stressors in relation to health: stressors and health in clinical work." Adv Psychosom Med 32: 58-71. LeResche, L. and S. F. Dworkin (2002). "The role of stress in inflammatory disease, including periodontal disease: review of concepts and current findings." Periodontol 2000 30: 91-103. McEwen, B. S. (1998). "Protective and damaging effects of stress mediators." N Engl J Med 338(3): 171-179. Huyser, B. and J. C. Parker (1998). "Stress and rheumatoid arthritis: an integrative review." Arthritis Care Res 11(2): 135-145. Baker, G. H. (1982). "Life events before the onset of rheumatoid arthritis." Psychother Psychosom 38(1): 173-177. Disclosure of Interest: None Declared